PSYCHOLOGICAL FEATURES OF SENSE OF JUSTICE OF TEACHERS OF THE EDUCATIONAL ORGANIZATIONS - A. Volkov; O. Chursinova (Вестник Северо-Кавказского федерального университета)
This article reveals the content of the concept of «legal consciousness)). Legal consciousness of teachers is considered as the difficult complex education including two interconnected components: legal ideology and legal psychology, individual knowledge of the teacher, its personal values and strong-willed potential. The legal psychology in turn includes such structural components of sense of justice of the teacher of the educational organization as: cognitive and informative, emotional and valuable, activity - regulatory. As a result of the conducted research the most important elements of legal consciousness of teachers among which backbone are defined are allocated: legal knowledge (legal awareness), relation to the right (estimates, beliefs, valuable orientations) and legal installations, relation to institutes of the right, objectiveness, legal activity.